Independently tunable plus-type DDCC-based voltage-mode universal biquad filter with MISO and SIMO types. (September 2017) - Lee, Chen-Nong
Abstract: This paper presents an independently tunable voltage-mode universal biquad filter using three plus-type differential difference current conveyors (DDCC+s), two grounded capacitors, three / four grounded resistors and one floating resistor. The proposed biquad filter can simultaneously realize all five universal filtering responses (lowpass, highpass, bandpass, notch, and allpass) in single-input multiple-output type (SIMO type) and also can provide all of them in multiple-input single-output type (MISO type) without changing the filter topology. The proposed circuit does not need component matching conditions to realize any filter responses for both MISO and SIMO types. On the other hand, the circuit also can realize another SIMO and MISO high-input impedance voltage-mode universal biquad filter with controllable gains and using only grounded passive components. In all cases, the proposed circuit not only permits orthogonal tunability of ω 0 and Q but also achieves independent tunability of ω 0 and ω 0 / Q by using only grounded resistors without the need of control factors matching conditions. No extra inverting or non-inverting amplifiers are required for realizing any filter responses, and all the active and passive sensitivities are low. HSPICE simulations with TSMC 0.18 µm 1P6M CMOS process technology and experimental results validate theoretical predictions.